Development and implementation of a remote patient monitoring program for heart failure: a single‐centre experience - Baginski, Bryana N. (ESC Heart Fail, 2021)
AIMS: Remote patient monitoring (RPM) in the management of heart failure (HF), including telemonitoring, thoracic impedance, implantable pulmonary artery pressure (PAP) monitors, and cardiac implantable electronic device (CIED)‐based sensors, has had varying outcomes in single platform studies. Uncertainty remains regarding the development of single‐centre RPM programs; additionally, no studies examine the effectiveness of dual platform RPM programs for HF. This study describes the implementation and outcomes of a dual platform RPM program for HF at a single centre. METHODS AND RESULTS: An RPM program was developed to include two platforms (e.g. CardioMEMS™ HF System and HeartLogic™ HF Diagnostic). To examine changes within each participant over time, study‐related outcomes including total hospitalizations (TH), total length of stay (TLOS), cardiac hospitalizations (CH), cardiac LOS (CLOS), and cardiac‐related emergency department (ED) visits were compared in two timeframes: 12 months pre‐enrolment and post‐enrolment into RPM. For 141 participants enrolled, there was a significant reduction in the likelihood of experiencing a CH by 19% (0.77 vs. 0.61 events/patient‐year; HR: 0.81, 95% CI: 0.67–0.97, P = 0.03) and a cardiac‐related ED visit by 28% (0.48 vs. 0.34 events/patient‐year; HR: 0.72, 95% CI: 0.55–0.93, P = 0.01). There was also a 51% decrease (SE = 1.41, 95% CI: 2.79–8.38 days, P < 0.001) and 62% decrease (SE = 1.24, 95% CI: 3.35–8.22 days, P < 0.001) in TLOS and CLOS, respectively. CONCLUSIONS: A dual platform RPM program for HF using structured education, RPM‐capable devices, and alert‐specific medication titration reduces the likelihood of experiencing a cardiac hospitalization and cardiac‐related ED visit in this single‐centre study.